2010
DOI: 10.1111/j.1528-1167.2009.02412.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of long‐term potentiation by valproic acid through modulation of cyclic AMP

Abstract: SUMMARYPurpose: Valproic acid (VPA) is widely used clinically in epilepsy, bipolar disorder, and migraine. In experimental models, it has also been shown to have neuroprotective and antiepileptogenic effects. Its mechanisms of action in these diverse conditions are, however, unclear, but there is some evidence indicating an effect of VPA upon protein kinase A (PKA) activity. We, therefore, asked whether VPA modulates cyclic adenosine monophosphate (cAMP)/PKA-dependent synaptic plasticity and whether this mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…Therefore, the inhibition of cPLA2 by VPA and PIA may be beneficial under these conditions. However, long term VPA treatment is associated with impairment of hippocampal synaptic plasticity (Sgobio et al, 2010) and in vitro 1 mM VPA reduced long term potentiation in hippocampal slices (Chang et al, 2010) indicating that VPA and PIA may also reduce activation of cPLA2 in normal synapses.…”
mentioning
confidence: 99%
“…Therefore, the inhibition of cPLA2 by VPA and PIA may be beneficial under these conditions. However, long term VPA treatment is associated with impairment of hippocampal synaptic plasticity (Sgobio et al, 2010) and in vitro 1 mM VPA reduced long term potentiation in hippocampal slices (Chang et al, 2010) indicating that VPA and PIA may also reduce activation of cPLA2 in normal synapses.…”
mentioning
confidence: 99%
“…(ii) Their study, which shows that repeated treatment with TAK-063 prevents striatal neurodegeneration, is focused on the mechanism by which TAK-063 blocks the reduction of BDNF levels. Our study showed that PF-2545920 enhances the excitability of pyramidal neurons and seizure activity possibly via activation of the cAMP–PKA pathway (Boulton et al, 1993; Chang et al, 2010; Lee, 2015). (iii) TAK-063, which has a faster off-rate, induces similar levels of activation in medium spiny neurons (MSNs) in the indirect pathway, while MSNs in the direct pathway are only partially activated (Suzuki et al, 2016).…”
Section: Discussionmentioning
confidence: 68%
“…Cyclic nucleotides, including cAMP and cGMP, act as second messenger signaling molecules and participate in numerous cellular functions in the CNS, including neurotransmitter specification, axon guidance, and refinement of neuronal connectivity (Averaimo and Nicol, 2014; Mu et al, 2014). In addition, a previous study showed that activation of the cAMP–PKA pathway increases excitability and enhances epileptiform activity in vitro (Boulton et al, 1993; Chang et al, 2010; Lee, 2015). …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been shown lithium increased activation of PKA leading to enhance the phosphorylation of GSK-3β80) and CREB in neuron-enriched cerebral cortical cultures from rats81) and in the intact rat brain 82). Conversely, VPA has been suggested to reduce forskolin-induced increase in cAMP levels in C6 rat glioma cells83) in the cultured cortical neurons84) and in the prefrontal cortex of rats 85). It remains unclear whether these mood stabilizers affect cAMP directly or indirectly by inhibiting the formation of cAMP.…”
Section: Main Subjectsmentioning
confidence: 99%